2021
DOI: 10.1159/000512757
|View full text |Cite
|
Sign up to set email alerts
|

Imagery Rescripting and Imaginal Exposure in Nightmare Disorder Compared to Positive Imagery: A Randomized Controlled Trial

Abstract: <b><i>Introduction:</i></b> Both imagery rescripting and imaginal exposure have been proven to be effective in the treatment of chronic nightmares when compared to a waitlist condition. Little is known about their comparative efficacy and their efficacy compared to an active control. <b><i>Objective:</i></b> The aims of this study were to compare the two treatments to one another and to positive imagery as an active control, and to explore covariates of the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…A recent study found rescripting, exposure and the active control condition (imagining a safe place) all equally effective in a randomized controlled trial of nightmare treatment (Schmid et al, 2021). The researchers compared imagery rescripting (IR) and imaginal exposure (IE) to an active versus waitlist control (positive imagery; PI) with 96 patients with nightmare disorder experiencing idiopathic nightmares.…”
Section: Nightmare Treatments: Variably Effective Underutilized and N...mentioning
confidence: 99%
“…A recent study found rescripting, exposure and the active control condition (imagining a safe place) all equally effective in a randomized controlled trial of nightmare treatment (Schmid et al, 2021). The researchers compared imagery rescripting (IR) and imaginal exposure (IE) to an active versus waitlist control (positive imagery; PI) with 96 patients with nightmare disorder experiencing idiopathic nightmares.…”
Section: Nightmare Treatments: Variably Effective Underutilized and N...mentioning
confidence: 99%
“…The emotional impact sub‐score is then closer to the criteria as defined by the DSM‐5 and the ICSD‐3. Additionally, the inclusion of complementary items about the recurrence of nightmares and their content, proves useful in clinical practice, particularly in PTSD and nightmare disorders treatments and while using techniques such as imagery rescripting (IRT), positive imagery, or imaginal exposure (Schmid et al, 2021; Waltman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 3 Results of the exploratory analysis of items of the NSI questionnaire among the 77 French included patients (Schmid et al, 2021;Waltman et al, 2018).…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation